2019
DOI: 10.1111/efp.12499
|View full text |Cite
|
Sign up to set email alerts
|

Identification of wood‐decay fungi and assessment of damage in log depots of Western Black Sea Region (Turkey)

Abstract: The aim of this study was to determine and quantify the wood‐decay fungi found on logs of forest tree species (beech, oak, hornbeam, Scots pine and fir) stored in log depots located in six different provinces in the Western Black Sea Region of Turkey. Additionally, it was aimed to determine the natural durability of some important wood species against the most commonly detected wood‐decay fungi. Eighteen families, 31 genera and 45 species belonging to the division Basidiomycota were detected; Antrodia crassa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
3
6
0
1
Order By: Relevance
“…Earlier studies in other countries have reported similarly that temperature, relative humidity, wood contact with soil and damp ground in the depots influence the abundance of wood-decay fungi and the severity of decay (Mueller et al, 2004;Talley et al, 2002;Yalçin et al, 2019). Fungal abundance and species variations have been reported as host-specific in several other studies (Deflorio et al, 2008;Malakani et al, 2014;Yalçin et al, 2019), corroborating the findings in the current work.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Earlier studies in other countries have reported similarly that temperature, relative humidity, wood contact with soil and damp ground in the depots influence the abundance of wood-decay fungi and the severity of decay (Mueller et al, 2004;Talley et al, 2002;Yalçin et al, 2019). Fungal abundance and species variations have been reported as host-specific in several other studies (Deflorio et al, 2008;Malakani et al, 2014;Yalçin et al, 2019), corroborating the findings in the current work.…”
Section: Discussionsupporting
confidence: 90%
“…Samples were returned to the laboratory, carefully dried at 40-45°C for 2 and 3 days to prevent deterioration (Yalçin et al, 2019) and finally stored in polythene bags for further studies.…”
Section: Sampling Of Sawmill Depots and Fungal Specimen Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the weight loss of the control samples of the wood species were examined, the weight losses were found higher in pine wood exposed brown rot than beech wood exposed white rot. This is due to the differences in the enzyme systems of fungi [12].…”
Section: Figure 4 Weight Loss In Beech Based On Carbonized Surfacesmentioning
confidence: 99%
“…Basidiomycota bölümüyle ilgili olarak, araştırma alanına yakın çevre ve komşu bölgelerde yapılan çalışmaların bulgularıyla mevcut çalışma arasında %7,84-21,52 düzeyinde (Tablo 1) benzerlik bulunmaktadır [3], [15], [16], [33]- [39]. Tablo 1'e göre Kocaeli yöresi için takson sayıları ve ilgili çalışmalar arasındaki benzerlik %21,52, Bartın-Küre Dağları Milli Parkı bölümü için %16,92 [36] olup yakın çevresi Bolu ve Düzce yöresinde 26 ortak taksonla en yüksek sayıya ulaşılmasına rağmen Yenmez Zehirli benzerlik oranı %10'dur [16].…”
Section: şEkil 4 Taksonların Yenilebilirliğiunclassified